Effect of Dietary Administration of Green Macroalgae (Ulva intestinalis) on Mucosal and Systemic Immune Parameters, Antioxidant Defence, and Related Gene Expression in Zebrafish (Danio rerio) - Elaheh Rouhani; Roghieh Safari; Mohammad Reza Imanpour; Seyed Hossein Hoseinifar; Metin Yazici; Ehab El-Haroun (Aquaculture Nutrition)
This study investigated the effects of adding green macroalgae gutweed (Ulva intestinalis) powder to zebrafish (Danio rerio) feed at different levels on innate immune responses, antioxidant defence, and gene expression. A total of 600 zebrafish (0.3±0.08 g) were randomly allocated to 12 aquariums in four treatments with three replicates (50 fish per aquarium). Zebrafish were fed with different levels of U. intestinalis powder 0, 0.25, 0.5, and 1% for eight weeks. Whole-body extract (WBE) immune parameters including total protein level, globulin level, and lysozyme activity were evaluated and revealed statistically significant increased in all U. intestinalis supplemented groups compared to the control (P<0.05). However, mucus immune parameters (total protein, globulin, and lysozyme) were statistically different in only 1% gutweed supplemented groups from other groups. While glutathione peroxidase (GPx) and superoxide dismutase (SOD) increased with the addition of gutweed (P<0.05), catalase (CAT) did not change (P>0.05). The study results showed that dietary gutweed remarkably upregulated immune-related genes such as lysozyme (Lyz) and Interleukin 1 beta (IL-1β). Antioxidant-related genes (SOD and CAT) and growth-related genes, including growth hormone (GH) and insulin-like growth factor-I (IGF-1), were remarkably upregulated with gutweed treatment (P<0.05). In conclusion, dietary U. intestinalis showed beneficial effects on immunity, and same effects were observed in case of antioxidant and growth related genes expression in zebrafish.